The impact of segregated diversity on the code of the street: an analysis of violence-related norms in selected post-industrial neighborhoods in Germany - Kurtenbach, Sebastian (International journal of conflict and violence, 2019)
Youth violence remains a concern in Germany, particularly in specific “risky” neighborhoods that tend to be socially segregated and ethnically diverse. In this paper we critically compare the results of twenty-seven qualitative interviews conducted in three risky neighborhoods in the German Ruhr area with the code of the street. While this theoretical framework is frequently cited in explaining youth violence, it was based on research in an ethnically homogenous neighborhood in the United States and thus does not engage with questions of diversity. Our findings show that the core of the code of the street is also applicable in heterogeneous contexts, thus extending the generalizability of the theoretical framework. Manifestations of manhood, reputation, and symbolic power were found to be major elements of street culture, although characterized somewhat differently than in the original work.